Polskie i holenderskie prawo karne środowiska – wybrane zagadnienia - Grabarczyk, Tymon (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
Despite the fact that the Directive 2008/99/EC of the European Parliament and the Council on the protection of the environment through criminal law has been in force for more than 10 years, and its relevant provisions were subsequently implemented into domestic legal systems, the area of the environmental criminal law has received limited attention in the academic research. The aim of this article is to present a comparative dimension of the environmental criminal law through an analysis of the legal bases of criminal liability of Polish and Dutch environmental law. The key legal acts in this regard,i.e. the Criminal Code of the Netherlands and the Economic Offences Act are the main subject of this survey. Moreover, the relevant provisions of Dutch law were compared with their counterparts.
Keywords: the Netherlands; environmental protection; criminal law; environmental criminal law; Dutch environmental criminal law